Dofetilide for the treatment of premature ventricular complexes and ventricular tachycardia in patients with structural heart disease. - Deshmukh, Amrish; Yokokawa, Miki; McBride, Daniel; Simpson, Jamie; Chou, Andrew; Ghannam, Michael; Liang, Jackson J.; Saeed, Mohammed; Cunnane, Ryan; Ghanbari, Hamid; Latchamsetty, Rakesh; Crawford, Thomas; et al. (Journal of Cardiovascular Electrophysiology, 2024)
Background: Dofetilide is a class III antiarrhythmic agent approved for the treatment of atrial fibrillation and atrial flutter. Given the efficacy of other class III agents, it has been used off‐label for the treatment of premature ventricular complexes (PVCs) and ventricular tachycardias (VTs). Objective: The purpose of this study was to determine the efficacy and safety of dofetilide for ventricular arrythmias (VAs). Methods: In this retrospective cohort study, 81 patients (59 men; age = 60 ± 14 years; LVEF = 0.34 ± 0.16) were admitted for dofetilide initiation to treat PVCs (29), VTs (42) or both (10). A ≥ 80% decrease in PVC burden was defined as a satisfactory response. An ICD was present in 72 patients (89%). Another antiarrhythmic was previously used in 50 patients (62%). Prior catheter ablation had been performed in 33 patients (41%). Results: During intitiation, dofetilide was discontinued in 12 patients (15%) due to QT prolongation (8) and inefficacy to suppress VAs (4). Among the 32 patients with PVCs who successfully started dofetilide, the mean PVC burden decreased from 20 ± 10% to 8 ± 8% at a median follow‐up of 2.6 months (p <.001). PVC burden was reduced by ≥80% in only 11/32 patients (34%). During 7 ± 1 years of follow‐up, 41/69 patients (59%) continued to have VAs and received appropriate ICD therapies for monomorphic VTs (35) and polymorphic VT/VF (6) at a median of 8.0 (IQR 2.6–33.2) months. Dofetilide had to be discontinued in 50/69 patients (72%) due to inefficacy or intolerance. The composite outcome of VT/VF recurrence, heart transplantation, or death occurred in 6/12 patients (50%) without dofetilide and 49/69 patients (71%) with dofetilide. The event free survival was similar between patients treated with and without dofetilide (log‐rank p =.55). Conclusions: Treatment with dofetilide was associated with a decrease in PVCs, however clinically significant suppression occurred in a minority of patients. Dofetilide failed to suppress the occurrence of VTs in a majority of patients.